Congenital and acquired ADAMTS13 deficiency: Two mechanisms, one patient. Issue 4 (4th November 2014) - Ferrari, Barbara; Cairo, Andrea; Pontiggia, Silvia; Mancini, Ilaria; Masini, Luciano; Peyvandi, Flora
Abstract : Thrombotic thrombocytopenic purpura (TTP) is a life‐threatening microangiopathy with a heterogeneous and largely unpredictable course. It is caused by ADAMTS13 deficiency, that can be either congenital or due to anti‐ADAMTS13 autoantibodies development. ADAMTS13 deficiency is necessary but not always sufficient to cause acute clinical manifestations and trigger factors may be needed. We report the case of a woman diagnosed with congenital TTP in her adulthood, presenting with anti‐ADAMTS13 autoantibodies in acute phase during ticlopidine consumption. Noteworthy, the two ADAMTS13 mutations identified in this patient are novel: one is a splice‐site mutation located in intron 11 (c.1308+2_5delTAGG) and the other is a point missense mutation in exon 29 (c.4184T>C leading to p.Leu1395Pro substitution). Since congenital TTP is an extremely rare disease and drug‐induced TTP is an uncommon side effect of treatment with ticlopidine, the simultaneous occurrence of both mechanisms of disease in one patient is exceptional. This case represents TTP as a multifactorial disease, with ADAMTS13 genetic abnormality and environmental exposures acting together in determining individual clinical phenotype. J. Clin. Apheresis 30:252–256, 2015. © 2014 Wiley Periodicals, Inc.